#MeToo and testimonial injustice: An investigation of moral and conceptual knowledge - Hänel, Hilkje C (Philosophy & Social Criticism, 2022)
Two decades ago, Tarana Burke started using the phrase ‘me too’ to release victims of sexual abuse and rape from their shame and to empower girls from minority communities. In 2017, actress Alyssa Milano made the hashtag #MeToo go viral. This article’s concern is with the role of testimonial practices in the context of sexual violence. While many feminists have claimed that the word of those who claim to being sexually violated by others (should) have political and/or epistemic priority, others have failed to recognize the harm and injury of instances of sexual violence that are not yet acknowledged as such and failed to listen to victims from marginalized social groups. In fact, some feminists have attacked #MeToo for mingling accounts of ‘proper’ sexual violence and accounts that are not ‘proper’ experiences of sexual violence. My aim in this article is to show why this critique is problematic and find a philosophically fruitful way to understand the #MeToo-movement as a movement that strives for moral and conceptual progress.
Keywords: #metoo; approches et analyses; cours; cycles supérieurs; discipline; fem9000; justice sociale; patriarcat; philosophie; racisme; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; violences sexistes et sexuelles; violences sexuelles

Contesting Islam, constructing race and sexuality: The inordinate desire of the West - Thobani, Sunera (Bloomsbury Academic, 2022)
Les affrontements politiques actuels de la « guerre contre le terrorisme » illustrent que l'interaction au sein et entre les civilisations dites occidentales et moyen-orientales est en constante évolution. Un thème récurrent est cependant la façon dont l'Islam et les musulman.e.s signifient « l'Ennemi » dans l'imaginaire socioculturel occidental et sont devenu.e.s « l'Autre » contre lequel l'Occident s'identifie. Dans un mélange unique et perspicace de théorie raciale critique, féministe et postcoloniale, Sunera Thobani examine comment l'islam est à la base de la formation de l'identité occidentale à des moments critiques de son histoire, y compris les croisades, la Reconquista et la période coloniale. Plus précisément, elle explore comment la masculinité et la féminité se forment à ces moments charnières et quel rôle le féminisme a joué dans les guerres contre l'islam « radical ». En exposant ces relations symbiotiques, Thobani explore comment le retour de la « religion » retravaille les politiques raciales, de genre et sexuelles par lesquelles la société occidentale se définit, et plus spécifiquement, se définit contre l'islam. Contester l'islam, construire la race et la sexualité déballe les orthodoxies conventionnelles et non conventionnelles pour ouvrir de nouveaux espaces dans la façon dont nous pensons à l'identité sexuelle et raciale en Occident et au rôle crucial que l'islam a eu et continue d'avoir dans son développement.
Keywords: antiracisme; approches et analyses; cours; discipline; fem3400; histoire et politique; personnes musulmanes; philosophie; premier cycle; racisme; sciences humaines; sexisme; sexualité; système colonial; systèmes d'oppressions; thématiques; violences